Defining Experiential Education: The field's seminal thinkers take stock and look ahead. - Green, Patrick; Kolb, Alice; Kolb, David; Kuh, George (Experiential Learning and Teaching in Higher Education, 2024)
Several decades into their remarkable careers, George Kuh and David & Alice Kolb continue to have an outsized influence on the field of experiential education. A 2022 survey conducted by the Society for Experiential Education (SEE) ranked Kuh and Kolb as the two scholars most relied on by current practitioners, without any close runners up. ELTHE invited them to think about why this is, what prompted them to get into this work, and where it might go next. The conversation was led by Patrick Green, member of the SEE Board of Directors and ELTHE Editorial Board, and chair of the SEE Research & Scholarship Committee. It has been edited and condensed.